2005
DOI: 10.1109/tpc.2005.849649
|View full text |Cite
|
Sign up to set email alerts
|

Media Richness or Media Naturalness? The Evolution of Our Biological Communication Apparatus and Its Influence on Our Behavior Toward E-Communication Tools

Abstract: Abstract-E-communication in businesses hasThe main goal of this paper is to extend prior research on human evolution and behavior toward technology [16], [17] and offer a solid theoretical basis on which the mixed findings above can be understood. The paper provides an alternative to the media richness hypothesis, referred to here as the media naturalness hypothesis, developed based on Darwin's theory of evolution by natural selection. Like the media richness hypothesis, the media naturalness hypothesis has im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
270
1
4

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 328 publications
(284 citation statements)
references
References 60 publications
9
270
1
4
Order By: Relevance
“…Media naturalness theory (Kock, 2005) holds that humans are biologically conditioned for face-to-face interaction, and digitally mediated communication should try to approximate a face-to-face experience. Kock (2005) outlines five communication elements to consider: colocation (sharing the same space); speech; facial expressions; synchronicity (the real-time back-and-forth nature of communication); and body language.…”
Section: Symposiummentioning
confidence: 99%
“…Media naturalness theory (Kock, 2005) holds that humans are biologically conditioned for face-to-face interaction, and digitally mediated communication should try to approximate a face-to-face experience. Kock (2005) outlines five communication elements to consider: colocation (sharing the same space); speech; facial expressions; synchronicity (the real-time back-and-forth nature of communication); and body language.…”
Section: Symposiummentioning
confidence: 99%
“…Cho, Ramgolam, Schaefer and Sandlin [8] studying the way in which synchronicity affects communication overload, found that the communicants felt heavier load with low synchronicity media, than with high synchronicity media. For this reason, Kock [15] argues that due to the long experience of people with face to face communication, they are more likely to choose to communicate through a high synchronicity medium, since it gives a closer to face to face experience.…”
Section: Media Naturalness Theorymentioning
confidence: 99%
“…This shows a positive attitude towards VW since it provides a PAPER EDUCATIONAL COMMUNICATION IN VIRTUAL WORLDS AND VIDEOCONFERENCE game-like condition which reduces emotional stress. Based on MNT [15], VW is considered a more natural communication medium than VC.…”
Section: F Communication's Proceduresmentioning
confidence: 99%
“…Particularly essential is research on the influence of the use of these tools over the quality of the emergent team mental model and ensuing team performance. & Dolan, 2005;Ekman, Friesen & Ancoli, 1980;Kock, 2005;Mehrabian, 1972).…”
Section: Information-sharing Toolsmentioning
confidence: 99%